The will to communicate - Perez, Diana Ines (2013)
In this paper I discuss Rodriguez-Pereyra’s claim according to which analytical philosophy should be published exclusively in English. I focus my reply on three issues: (1) the implicit conception of philosophy and of the philosophical practice that underlies his argument, (2) the myth of the “native speaker” and (3) some values that should guide philosophy and which I propose to highlight.